The big switch : rewiring the world, from Edison to Google - Carr, Nicholas G., 1959- (New York : Norton, 2008)
A hundred years ago, companies stopped producing their own power with steam engines and plugged into the newly built electric grid. The cheap power pumped out by electric utilities not only changed how businesses operated but also brought the modern world into existence. Today a similar revolution is under way. Companies are dismantling their private computer systems and tapping into rich services delivered over the Internet. This time it's computing that's turning into a utility. The shift is already remaking the computer industry, bringing new competitors like Google to the fore and threatening traditional stalwarts like Microsoft and Dell. But the effects will reach much further. Cheap computing will ultimately change society as profoundly as cheap electricity did. Here, business journalist Carr weaves together history, economics, and technology to explain why computing is changing--and what it means for all of us.--From publisher description.
Burden's wheel -- The inventor and his clerk -- Digital millwork -- Goodbye, Bill Gates -- The White City -- World Wide Computer -- From the many to the few -- The great unbundling -- Fighting the net -- A spider's web -- iGod -- Flame and filament.
Bibliografische referenties ; index
Keywords: Computers and civilization; Information technology -- Social aspects; Internet; Technological innovations